How Does Nutritional Status Affect Outcomes in Patients with Neurological Diseases? - Şükran GÜZEL; Eda GÜRÇAY; Ebru KARACA UMAY; Serdar MERCİMEKÇİ; Aytül ÇAKCI (Tehran University of Medical Sciences, 2020)
Background: To evaluate the nutritional status of patients with neurological diseases during the rehabilitation process and to investigate the relationships between the nutritional status and disease severity and clinical evaluation outcomes. Methods: In this prospective trial, 109 patients with a disease duration of <6 months, hospitalized for neurological rehabilitation in Physical Medicine and Rehabilitation Clinic, Ankara, Turkey were enrolled from 2014-17. All patients were assessed with the Mini Mental State Examination (MMSE) test, European Quality of Life Scale (Euro-QoL), Hospital Anxiety and Depression Scale (HADS), Pittsburg Rehabilitation Participation Scale (PRPS), and Functional Ambulation Category (FAC). Nutritional status was analyzed by biochemical and anthropometric parameters. The patients received a conventional rehabilitation program and a nutritional support according to clinical and laboratory findings for 4 weeks. The outcome data were evaluated at baseline and at the end of 4-week treatment. Results: Linear regressions analysis revealed that the significant independent predictors that associated positively with baseline insulin (P=0.010) and negatively with baseline cortisol (P=0.020) levels were Brunnstrom upper and hand stages. Additionally, the significant independent predictor that associated positively with baseline insulin (P=0.041) was Brunnstrom lower stage. Conclusion: Insulin and cortisol levels may be predictors in motor function recovery of stroke patients in rehabilitation process. Early detection and treatment of malnutrition both during hospitalization and follow-up might be important for the improvement of outcomes.